The proposal - Balogh, Mary (Balogh, Mary. Survivors' Club series., 2012)
Gwendoline, Lady Muir, has seen her share of tragedy, especially since a freak accident took her husband much too soon. Content in a quiet life with friends and family, the young widow has no desire to marry again. But when Hugo, Lord Trentham, scoops her up in his arms after a fall, she feels a sensation that both shocks and emboldens her. Hugo never intends to kiss Lady Muir, and frankly, he judges her to be a spoiled, frivolous, if beautiful, aristocrat. He is a gentleman in name only: a soldier whose bravery earned him a title; a merchant's son who inherited his wealth. He is happiest when working the land, but duty and title now demand that he finds a wife. He does not wish to court Lady Muir, nor have any role in the society games her kind thrives upon. Yet Hugo has never craved a woman more; Gwen's guileless manner, infectious laugh, and lovely face have ruined him for any other woman. He wants her, but will she have him? The hard, dour ex-military officer who so gently carried Gwen to safety is a man who needs a lesson in winning a woman's heart. Despite her cautious nature, Gwen cannot ignore the attraction. As their two vastly different worlds come together, both will be challenged in unforeseen ways. But through courtship and seduction, Gwen soon finds that with each kiss, and with every caress, she cannot resist Hugo's devotion, his desire, his love, and the promise of forever.